Antimony contamination and its risk management in complex environmental settings: A review. (January 2022) - Bolan, Nanthi; Kumar, Manish; Singh, Ekta; Kumar, Aman; Singh, Lal; Kumar, Sunil; Keerthanan, S.; Hoang, Son A.; El-Naggar, Ali; Vithanage, Meththika; Sarkar, Binoy; Wijesekara, Hasintha; et al.
Graphical abstract: Abstract: Antimony (Sb) is introduced into soils, sediments, and aquatic environments from various sources such as weathering of sulfide ores, leaching of mining wastes, and anthropogenic activities. High Sb concentrations are toxic to ecosystems and potentially to public health via the accumulation in food chain. Although Sb is poisonous and carcinogenic to humans, the exact mechanisms causing toxicity still remain unclear. Most studies concerning the remediation of soils and aquatic environments contaminated with Sb have evaluated various amendments that reduce Sb bioavailability and toxicity. However, there is no comprehensive review on the biogeochemistry and transformation of Sb related to its remediation. Therefore, the present review summarizes: (1) the sources of Sb and its geochemical distribution and speciation in soils and aquatic environments, (2) the biogeochemical processes that govern Sb mobilization, bioavailability, toxicity in soils and aquatic environments, and possible threats to human and ecosystem health, and (3) the approaches used to remediate Sb-contaminated soils and water and mitigate potential environmental and health risks. Knowledge gaps and future research needs also are discussed. The review presents up-to-date knowledge about the fate of Sb in soils and aquatic environments and contributes to an important insight into the environmental hazards of Sb. The findings from the review should help to develop innovative and appropriate technologies for controlling Sb bioavailability and toxicity and sustainably managing Sb-polluted soils and water, subsequently minimizing its environmental and human health risks.